Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1155/2018/4780615
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Anesthetic Protects Hepatocyte from Reactive Oxygen Species‐Induced Cellular Apoptosis during Liver Transplantation In Vivo

Abstract: Background Liver transplantation leads to liver ischemia/reperfusion (I/R) injury, resulting in early graft dysfunction and failure. Exacerbations of oxidative stress and inflammatory response are key processes in the development of liver I/R injury. Intravenous anesthetic propofol potent effects on free radical scavenging and protects livers against I/R injury. However, the role and mechanism of propofol-mediated hepatic protection in liver transplantation is poorly understood. The aim of this study was to ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…26 Propofol PostC, however, has been demonstrated to reduce hepatic I/R injury by inhibiting Nox following liver transplantation. 27 The present study showed that PostC decreased Cybb expression in cases of I/R injury.…”
Section: Statisticssupporting
confidence: 58%
See 1 more Smart Citation
“…26 Propofol PostC, however, has been demonstrated to reduce hepatic I/R injury by inhibiting Nox following liver transplantation. 27 The present study showed that PostC decreased Cybb expression in cases of I/R injury.…”
Section: Statisticssupporting
confidence: 58%
“…It was shown that Nox proteins contributed to the action mechanisms of preconditioning (PreC) and that Cybb was required for the activation of the protective effect of PreC in myocardial I/R models 26 . Propofol PostC, however, has been demonstrated to reduce hepatic I/R injury by inhibiting Nox following liver transplantation 27 . The present study showed that PostC decreased Cybb expression in cases of I/R injury.…”
Section: Discussionmentioning
confidence: 47%
“…Kidney tissues (100 mg) were homogenized, and a bicinchoninic acid protein assay was used to quantify the protein levels. A heparin binding protein primary antibody (1:1000, Abcam, USA) was used for Western blotting, which was performed as described in our previous study [39].…”
Section: Western Blottingmentioning
confidence: 99%
“…There is a close interdependence between oxidative stress and neuroinflammation. Increases in intracellular ROS are known to promote NF- κ B activation, which subsequently regulates the transcription of proinflammatory cytokines and other mediators involved in acute inflammation [ 47 , 48 ]. Dexmedetomidine has been reported to prevent NF- κ B translocation into the nucleus and thus reduce the production of proinflammatory cytokines, thus exerting a protective effect against brain damage [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%